PENERAPAN MODEL PEMBELAJARAN OSBORN UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN ION DAN PH LARUTAN GARAM DI KELAS XI IPA SMA NEGERI 14 PEKANBARU - Lutfiah Azmi; Betty Holiwarni; Rasmiwetti Rasmiwetti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2020)
The research aims to improve student learning achievement on the subject of ion equilibrium and pH of salt solution in class XI IPA SMAN 14 Pekanbaru. This type of research is an experimental study with a pretestposttest design. The research was conducted at SMAN 14 Pekanbaru. The sample from the study was students of class XI IPA 1 as an experimental class and students in class XI IPA 3 as a control class. The experimental class is the class applied to the Osborn learning model while the control class is not treated. The data analysis technique used is the t-test. Based on the results of the data analysis test, tcount> ttable is 7.25> 1.67, meaning that the application of Osborn's learning model can improve student learning achievement on the subject of ion equilibrium and pH of salt solution in class XI IPA 14 of SMA Negeri 14 with categories of achievement improvement learning in the experimental class based on Score (N-Gain) is high, which is 0.73.